Global, regional, and national prevalence and disability-adjusted life-years for endometriosis in 204 countries and territories, 1990–2019: Findings from a global burden of disease study - Dong Yi Shen; Jing Li; PanWei Hu; Cong Qi; Hong Yang (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Introduction: This study aimed to analyze the worldwide, regional burden of endometriosis and its trends from 1990 to 2019, utilizing the latest data from Global Burden of Disease (GBD) 2019. GBD 2019 is a global database tool for comprehensive analysis and an important result of long-term collaboration among governments worldwide. Methods: We utilized the Global Health Data Exchange Query tool to analyze endometriosis in prevalence numbers, age-standardized prevalence rates (ASPR), and disability-adjusted life-years (DALYs) from 1990 to 2019 in 204 countries and regions. Additionally, this study investigated the impacts of period, age, and cohort on the prevalence and DALYs of endometriosis from the global perspective and in the five sociodemographic index (SDI) regions. Results: Among the 21 regions, the most significant reduction in the prevalence of endometriosis between 1990 and 2019 occurred in Central Latin America. In 204 countries, the most pronounced decline was observed in Guatemala. At the SDI level, with the increase of SDI, the ASPR of endometriosis in all regions worldwide showed an overall decreasing trend. The prevalence of endometriosis peaked between the ages of 25 and 29. Discussion: The findings of this study reflect the temporal and spatial tendency of the burden of endometriosis during the study period, and provide a reference for health agencies around the world to formulate policies on endometriosis, so as to reduce the harm of endometriosis to women worldwide.